2019
DOI: 10.7554/elife.46846
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive intestinal peptide-expressing interneurons are impaired in a mouse model of Dravet syndrome

Abstract: Dravet Syndrome (DS) is a severe neurodevelopmental disorder caused by pathogenic loss of function variants in the gene SCN1A which encodes the voltage gated sodium (Na+) channel subunit Nav1.1. GABAergic interneurons expressing parvalbumin (PV-INs) and somatostatin (SST-INs) exhibit impaired excitability in DS (Scn1a+/-) mice. However, the function of a third major class of interneurons in DS – those expressing vasoactive intestinal peptide (VIP-IN) –is unknown. We recorded VIP-INs in brain slices from Scn1a+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
91
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(97 citation statements)
references
References 63 publications
5
91
1
Order By: Relevance
“…Despite extensive studies of these models, the neuronal basis of Dravet and the mechanisms underlying the different stages are still debated, with evidence in favor of reduced function of inhibitory neurons, or enhanced function of excitatory neurons. In support of the "inhibitory neuron" hypothesis, electrophysiological studies demonstrated impaired firing of multiple types of inhibitory neurons during the worsening stage, with no apparent change in the excitability of excitatory neurons (De Stasi et al, 2016;Favero et al, 2018;Goff and Goldberg, 2019;Han et al, 2012;Ogiwara et al, 2007;Rubinstein et al, 2015bRubinstein et al, , 2015aTai et al, 2014;Tsai et al, 2015). Moreover, selective deletion of Scn1a in inhibitory neurons was sufficient to cause seizures and premature mortality Kalume et al, 2013;Kuo et al, 2019;Ogiwara et al, 2013;Rubinstein et al, 2015a).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Despite extensive studies of these models, the neuronal basis of Dravet and the mechanisms underlying the different stages are still debated, with evidence in favor of reduced function of inhibitory neurons, or enhanced function of excitatory neurons. In support of the "inhibitory neuron" hypothesis, electrophysiological studies demonstrated impaired firing of multiple types of inhibitory neurons during the worsening stage, with no apparent change in the excitability of excitatory neurons (De Stasi et al, 2016;Favero et al, 2018;Goff and Goldberg, 2019;Han et al, 2012;Ogiwara et al, 2007;Rubinstein et al, 2015bRubinstein et al, , 2015aTai et al, 2014;Tsai et al, 2015). Moreover, selective deletion of Scn1a in inhibitory neurons was sufficient to cause seizures and premature mortality Kalume et al, 2013;Kuo et al, 2019;Ogiwara et al, 2013;Rubinstein et al, 2015a).…”
Section: Introductionmentioning
confidence: 84%
“…3C, D and Table 1A). Firing of PV-positive inhibitory neurons in DS mice was recently shown to depend on the ratio between sodium and potassium currents (Goff and Goldberg, 2019). Similarly, impaired inhibitory function at the worsening stage may be due to a combination of reduced sodium conductance together with developmental upregulation of potassium channels (Downen et al, 1999;Falk et al, 2003;Goldberg et al, 2011).…”
Section: The Level Of O-lm Interneurons Dysfunction Correlates With Tmentioning
confidence: 99%
“…SST+ INs play a prominent role in development, directing synapse formation (Oh et al, 2016), circuit maturation (Tuncdemir et al, 2016), and sensory integration (Marques-Smith et al, 2016). Third, dysfunction of VIP+ INs is found in models of neurodevelopmental psychiatric disorders pointing to an important role for this type of interneuron in early development (Batista-Brito et al, 2017;Goff and Goldberg, 2019;Mossner et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunction in one or more of these inhibitory neuron populations can disrupt both the feedback and feedforward inhibitory circuitry, resulting in epilepsy disorders (Khoshkhoo et al, 2017;Paz and Huguenard, 2015). NAV1.1 is predominantly localized in the soma and in the axon initiating segment of PV-positive neurons (Ogiwara et al, 2007) and to lesser extent in SST and VIP neurons (Goff and Goldberg, 2019;Li et al, 2014;Ogiwara et al, 2007;Tai et al, 2014). Reduced excitability of PV neurons has been implicated in hyperexcitable circuits in Scn1a mouse models of DS and GEFS+ (Dutton et al, 2013;Favero et al, 2018;Hedrich et al, 2014;Rubinstein et al, 2015a;Tai et al, 2014).…”
Section: Effects Of Scn1a Mutations On Neuronal Firingmentioning
confidence: 99%
“…Selective deletion of Nav1.1 in PV or SST-expressing neurons resulted in reduced neuronal excitability but led to phenotypically distinct behavioral disorders, suggesting distinct roles of interneurons subpopulations in mediating DS phenotypes (Rubinstein et al, 2015a). Recently, irregular spiking of VIP interneurons has been associated with DS phenotypes in an Scn1a +/mouse model (Goff and Goldberg, 2019), emphasizing the need to focus on multiple subtypes of interneuron population to more thoroughly understand how impaired neuronal firing contributes to seizure phenotypes in GEFS+ and other Scn1a mouse models.…”
Section: Effects Of Scn1a Mutations On Neuronal Firingmentioning
confidence: 99%